1981
DOI: 10.1002/chin.198141271
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: REACTIONS OF OXAZAPHOSPHOLANES WITH CARBOXYLIC ACIDS

Abstract: Das 2‐Diethylamino‐ 1,3,2‐Oxazaphospholan (I) reagiert mit Essigsäure (II) zur Zwischenstufe (III), die ohne Isolierung direkt einer Todd‐Atherton‐Reaktion unterworfen wird, wobei man das 1,3,2‐Oxazaphospholan (IV) erhält.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Attention is focused on the design of phosphorus-containing heterocycles. It was shown that phosphorus-containing reagents whose molecules contain two or three amido groups readily phosphorylate equimolar amounts of 1,2- and-1,3-amino alcohols including derivatives of 1,2-ethanolamine, ,,,, 1,3-propanolamine, , and prolinol , to afford 1,3,2-oxazaphospholanes (Scheme ) and -phosphorinanes. 1-Desoxy-1-aminosaccharides and 1- N -hydroxyethyl-3-iminopyrazoline are phosphorylated in a similar way.…”
Section: B Phosphorylation Of Amino Alcohols and O-amino Phenolsmentioning
confidence: 99%
See 3 more Smart Citations
“…Attention is focused on the design of phosphorus-containing heterocycles. It was shown that phosphorus-containing reagents whose molecules contain two or three amido groups readily phosphorylate equimolar amounts of 1,2- and-1,3-amino alcohols including derivatives of 1,2-ethanolamine, ,,,, 1,3-propanolamine, , and prolinol , to afford 1,3,2-oxazaphospholanes (Scheme ) and -phosphorinanes. 1-Desoxy-1-aminosaccharides and 1- N -hydroxyethyl-3-iminopyrazoline are phosphorylated in a similar way.…”
Section: B Phosphorylation Of Amino Alcohols and O-amino Phenolsmentioning
confidence: 99%
“…Subsequently, this reaction has been further developed regarding its use for synthetic purposes. ,,,, It became clear that excess acid is needed to neutralize the secondary amine being evolved, because the amine can attack the carbonyl group in acyl phosphite as a hard nucleophile. In fact, the use of equimolar amounts of the reactants gives a totally different result (Scheme ). , …”
Section: Phosphorylation Of Carboxylic Acidsmentioning
confidence: 99%
See 2 more Smart Citations